Polymorphs of molybdenum trioxide as innovative antimicrobial materials. Issue 4 (1st December 2013) - Lackner, Maximilian; Meier, Markus; Shafaei, Shahram; Zollfrank, Cordt; Plank, Johann; Guggenbichler, Joseph P.
Abstract : Environmental surfaces and their role in the incidence of nosocomial infections are the most common causes that affect hospitalized patients. Several approaches have been developed in surface technology, which offer an opportunity for investigation of novel materials with antimicrobial activity to avoid colonization of harmful microorganisms on non-living surface. Inorganic materials such as metals and metal oxides represent increasingly important materials as antimicrobial agents for numerous biological, chemical, biomedical and pharmaceutical applications. In this study, the morphology effect of molybdenum trioxides on their antimicrobial activity is reported. Our empirical results show that the crystal structures of molybdenum oxides including orthorhombic, monoclinic and hexagonal polymorphs exhibit an excellent to good antimicrobial activity, respectively. The authors suggest that molybdenum oxides can prevent the growth of various harmful microorganisms because of their different crystals and might be also reason of their different specific surface areas. These materials can provide a long-lasting antibacterial effect and are ideal for inanimate surfaces, which can be used in public and healthcare environments.